Red disperse dyes (DR 60, DR 73 and DR 78) at environmentally realistic concentrations impact biochemical profile of early life stages of zebrafish (Danio rerio) - Meireles, Gabriela; Daam, Michiel A.; Sanches, Ana Letícia Madeira; Zanoni, Maria V.B. [UNESP]; Soares, Amadeu M.V.M.; Gravato, Carlos; Oliveira, Danielle P. de (Elsevier, 2018)
Dyes have been used for more than twenty thousand years in textile, pharmaceutical, food, cosmetic, and photographic industries, among others. Despite their importance in these applications, dyes can be toxic and resistant to many degradation processes used in wastewater treatment plants. Although a large number of dyes have been released in the environments in high amounts, studies into the environmental toxicity of these substances are still scarce. The aim of this study was to evaluate the potential toxic effects of textile dyes Disperse Red 60, Disperse Red 73 and Disperse Red 78 in zebrafish early life stages. To this end, biochemical biomarkers were selected to evaluate non-enzimatic antioxidant (Total Glutathione), antioxidant enzymes (Glutathione S-transferase and Catalase), oxidative stress (lipid peroxidation), neurotransmission (acetylcholinesterase) and energetic metabolism parameters (energy available and energy consumed) after 96 h exposure to these dyes. Our results demonstrated that these disperse dyes induce biochemical alterations in zebrafish embryos at environmental realistic concentrations and that the discharge of these disperse dyes into water bodies should be carefully evaluated. The selected biomarkers were sensitive as early-warning endpoints of disperse dyes toxicity on zebrafish embryos. Implications for risk assessment and indications for future research are discussed.
Keywords: Cellular energy allocation; Neurotoxicity; Oxidative stress; Textile dyes